LEGAL STATUS OF THE DIGITAL PROFILE OF THE SUBJECTS OF CIVIL LEGAL RELATIONS - Rozhkova, Anna; Andreyanova, Inna (Administrative and Criminal Justice, 2021)
The aim of the work is a legal risk assessment to identify subjects of civil relations in order to implement commercial transactions safely using a digital profile. The paper attempts to assess the digital transformation of civil relations and the implementation of legal regulators for the protection and security of the subjects’ digital profile of. The aspects of “digital profile’s” definition interpretation as well the legal status separate signs for citizens and business entities of the notification procedure, differentiation of both rights to dispose and to use are reflected. The law enforcement practice of civil transactions in the course of digital resources’ turnover, as well as the attraction and imposition of administrative penalties are proposed, and a number of conflicts is identified due to the latency of illegal actions, the lack of digital competent human rights bodies and digital investigative tools.